FLOUTS OF THE COOPERATIVE PRINCIPLE MAXIMS IN SBYâ€™S PRESIDENTIAL INTERVIEWS - Fahrus Zaman Fadhly (English Review: Journal of English Education, 2012)
Abstract: This paper analyzed the presidential interviews of the President of Republic ofÂ Indonesia, Susilo Bambang Yudoyono (SBY), based on Griceâ€™s theory of the CooperativeÂ Principles (CP). This study employed a qualitative research design and the data wereÂ three transcripts of interview discourse between SBY and eight Indonesian journalistsÂ obtained through the presidential ofï¬cial website: http://www.presidentsby.info.Â The research investigated the ways of SBY in ï¬‚outing the CP maxims in his presidentialÂ interviews and the functions of the ï¬‚outs were. The research revealed that SBY ï¬‚outedÂ all the CP maxims and the maxim of Quantity was frequently ï¬‚outed. Meanwhile, thereÂ were four ways used by SBY in ï¬‚outing the CP maxims, i.e. hedging, indirectness, openÂ answer and detailed element. The function of the ï¬‚outs, i.e. face saving acts (FSA), selfprotection,Â awareness, politeness, interestingness, control of information, elaborationÂ andÂ ignorance. This research also revealed that CPÂ maxims of Grice are not universal.Â TheÂ phenomena of CP Maxim ï¬‚outsÂ in SBYâ€™s presidential interviews did not reduce theÂ cooperativeness.Â Over- information may help interviewers to achieve a rich backgroundsÂ andin-depth understanding of a phenomenon.Â Keywords:Â ï¬‚outs,Â maxim,Â cooperativeÂ principles, SBY, presidentialÂ interview